Growth performance, feed utilization efficiency and blood biochemical parameters of Nusuri chicken population of Odisha in floor rearing system - MOHANTA, N B; SAMAL, L; BEHURA, N C; PATI, P K; MAITY, A; BAGH, J (The Indian Journal of Animal Sciences, 2022)
A study was conducted to evaluate the performance of indigenous Nusuri chicken germplasm of Odisha maintained in floor rearing system. Seventy birds were selected for this study. Body weight and feed consumption were recorded up to 20 weeks. Feed conversion ratio (FCR), energy efficiency ratio (EER) and protein efficiency ratio (PER) were calculated. The body conformation traits (breast angle, body length, keel bone length, shank length, shank width, shank circumference, body girth, beak length, head width and height of the bird) were measured at 8th, 12th, 16th and 20th week of age. Blood was collected for estimation of haematological and serum biochemical parameters at 20th week. The day-old, 8th, 16th and 20th week body weights were 24.15, 250.92, 767.09 and 1033.38 g, respectively. The mean cumulative 8th and 20th weeks FCR was 3.74 and 5.46, respectively. The mean cumulative EER and PER was 9.07 and 1.23 at 8th week and 7.39 and 1.15 at 20th week, respectively. All recorded linear body measurements were higher in male birds than the female birds. Haematological parameters such as haemoglobin (12.27 g%), total erythrocyte count (3.57 mm3), total leucocyte count (9.80 mm3), packed cell volume (44.64%), mean corpuscular haemoglobin (39.49 pg), mean corpuscular volume (124.99 fL) and mean corpuscular haemoglobin concentration (27.84 g%) and serum biochemical parameters such as glucose (142.61 mg%), total protein (2.91 g%), albumin (1.86 g%), globulin (1.05 g%), urea (4.79 mg/dL), uric acid (6.00 mg/dL), cholesterol (106.74 mg/dL) and triglycerides (35.25 mg/dL) were recorded. This study provides a baseline data of growth performance, nutrient efficiency and blood metabolites of Nusuri chicken germplasm of Odisha.